Effect of cold and warm compress therapy on tissue temperature in healthy dogs - Millard, Ralph P. (Kansas State University, 2012)
Objective – To measure the effect of cold and warm compress therapy on tissue temperature in healthy dogs. Design – Controlled, blinded, crossover study Animals – 10 healthy mixed breed dogs Procedures – Dogs were sedated with hydromorphone 0.1 mg/kg IV and diazepam 0.25 mg/kg IV. Thermocouple needles were inserted to 0.5 cm (superficial), 1.0 cm (mid) and 1.5 cm (deep) into a shaved, lumbar, epaxial region to measure tissue temperature. Cold 2° F (-16.8° C) and warm 117°F (47°C) compresses were applied with gravity dependence for periods of 5, 10 and 20 minutes. Control data was collected under identical sedation. Results – Mean temperature significantly decreased after 5 minutes of cold application at only the superficial depth. Application of cold for 10 and 20 minutes significantly reduced the temperature at all depths. Twenty minutes of cold application significantly decreased temperature at only the mid depth compared to 10 minutes of application. Warm compresses significantly increased temperature at all depths after 10 minutes of application. Temperatures associated with 20 minutes of warm application were not significantly different than 10 minutes of application. Conclusions – When utilizing these methods of cold and warm compression, minimum time of application should be 10 minutes. Minimal changes occur by increasing cold application to 20 minutes and no changes occur when increasing heat application to 20 minutes. There is minimal to no change at depths ≥ 1.5 cm when using this method of heat application. Changes in tissue temperature and side effects of application longer than 20 minutes and in the absence of mu agonist opioids require further evaluation.
Keywords: Tissue Temperature; Compress; Biology, Animal Physiology (0433)